Comorbidity and quality of life in childhood cancer survivors treated with proton beam therapy. Issue 10 (29th October 2017) - Fukushima, Hiroko; Fukushima, Takashi; Suzuki, Ryoko; Iwabuchi, Atsushi; Hidaka, Kyoko; Shinkai, Toko; Masumoto, Kouji; Muroi, Ai; Yamamoto, Tetsuya; Nakao, Tomohei; Oshiro, Yoshiko; Mizumoto, Masashi; et al.
Abstract: Background: The rate of childhood cancer survival has recently reached >80%. Various adverse events among childhood cancer survivors (CCS) have been reported. Proton beams are able to avoid unnecessary irradiation to normal/vital organs. We conducted a quality of life (QOL) study for CCS who were treated with proton beam therapy (PBT). Methods: We included those patients treated with PBT to the brain, head, or neck and who were ≤15 years old at the University of Tsukuba Hospital between 1983 and 2011. Clinical information was collected from medical records. Questionnaires including the Pediatric Quality of Life Inventory (PedsQL) 4.0 Generic Core Scales (which assess health‐related quality of life) were sent to the families/patients. Results: Sixty patients were included. Median age at treatment was 6.2 years. The number of patients with status alive/dead/unknown was 32/24/4. Median follow‐up period was 63.0 months (range, 48–340 months) for survivors. Questionnaires were sent to 25 families/patients and 19 were returned. PedsQL was assessed for 17 patients. Eleven of 32 living patients had at least one comorbidity grade 3/4. Average QOL score was above that for Japanese schoolchildren and adolescents. There was no correlation with comorbidity, and only longer time from treatment was correlated with a higher PedsQL score ( P  =   0.006). Conclusion: CCS who were treated with multimodal treatment using PBT had a higher QOL score. Higher score was related to longer time since treatment, regardless of comorbidity.